Bipyridyl palladium embedded porous organic polymer as highly efficient and reusable heterogeneous catalyst for Suzuki–Miyaura coupling reaction. Issue 41 (11th April 2016) - Wang, Chang-An; Han, Yin-Feng; Li, Yan-Wei; Nie, Kun; Cheng, Xue-Li; Zhang, Jian-Ping
Abstract : Bipyridyl-palladium catalyst embedded porous organic polymers (Bpy-Pd-POP ) was synthesized and used as highly effective and reusable heterogeneous catalyst for the Suzuki–Miyaura coupling reaction. Abstract : Two robust porous organic polymers embedded with bipyridyl ligand (Bpy-POP ) were obtained via a bottom-up strategy. After a simple post-treatment, a Pd(ii )-containing POP (Bpy-Pd-POP ) was used as highly efficient and reusable heterogeneous catalyst for the Suzuki–Miyaura coupling reaction. It could be reused at least 15 times without significant loss of the catalytic activity (97–99% yield).